MicroRNA-92 expression may be associated with reduced estrogen receptor β1 mRNA levels in cervical portion of uterosacral ligaments in women with pelvic organ prolapse. (March 2016) - He, Ke; Niu, Gang; Gao, Jun; Liu, Jun-Xiu; Qu, Hu
Abstract: Objective: This study examined microRNA-92 (miR-92) expression level in relation to the mRNA level of its potential target gene, estrogen receptor β1 ( ERβ1 ), in female patients diagnosed with pelvic organ prolapse (POP). Study design: Between July 2012 and September 2014, a total of 104 patients were recruited at the First Affiliated Hospital of Sun Yat-sen University, which included 56 POP patients and 48 non-POP control subjects. Based on POP-Q score, the POP patients were further categorized into POP II and POP III groups. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to quantify miR-92 expression level. ERβ1 tissue expression was measured by western blot and immunohistochemistry (IHC) methods. SPSS 19.0 software was used for statistical analysis. Results: No remarkable differences were observed between the POP group and non-POP group, and between the POP II and POP III groups, with respect to age, body mass index (BMI), parity, menopause status, and family history of POP. The expression level of miR-92 in the POP group was dramatically higher than the non-POP group ( P < 0.05). Consistent with the disease status, miR-92 expression level in POP III group was markedly higher than the POP II group ( P < 0.05). Western blot analysis revealed significantly reduced levels of ERβ1 in the POP group compared to the non-POP group, with similar results obtained between the POP III and POP II groups (all P < 0.05). IHC results showed ERβ1 staining mainly in the nucleus and semi-quantitative measurements, expressed as positive expression rate, revealed that ERβ1 level in the POP group was clearly lower than non-POP group. Finally, statistical analysis of IHC results from uterosacral ligament tissue showed inverse correlation between miR-92 and ERβ1 expression levels in POP patients ( P < 0.05). Conclusions: Our results revealed increased miR-92 expression and decreased ERβ1 level in uterosacral ligaments of women diagnosed with POP, compared to non-POP subjects POP III patients exhibited more severe changes than POP II patients. Further, ERβ1expression is inversely correlated to miR-92 expression. Taken together, our results suggest that miR-92 and ERβ1 expression levels may be used as reliable diagnostic markers for assessing the severity of POP.